Exploring Visceral Fat as a Screening Marker for Cardiometabolic Risk in Children and Adolescents - Xia Wang; Hong Cheng; Jingfan Xiong; Junting Liu; Hongbo Dong; Liwan Fu; Xiangjun Xie; Xinying Shan; Xiaoyuan Zhao; Yinkun Yan; Pei Xiao; Jie Mi (Children)
Objective: To establish and validate age- and sex-specific visceral fat area (VFA) cutoff values for the effective identification of cardiometabolic risk (CMR) in children and adolescents. Methods: A cross-sectional study involving 8133 participants was conducted to derive age- and sex-specific VFA cutoffs, which were validated in a longitudinal cohort comprising 10,805 individuals. The predictive performance of the derived VFA cutoffs for CMR was evaluated using the area under the receiver operating characteristic curve (AUC). Additionally, logistic regression models were utilized to calculate the relative risk (RR) of CMR associated with elevated VFA levels. Results: The 75th percentile of the VFA was identified as the optimal cutoff for screening for hypertension, hyperglycemia, dyslipidemia, and CMR clustering in boys. In girls, the 75th percentile was optimal for screening hypertension, dyslipidemia, and CMR clustering, while the 80th percentile proved best for hyperglycemia. No significant difference in predicative performance was observed between the optimal and simplified VFA cutoffs. Longitudinal validation demonstrated that individuals exceeding the VFA cutoff had a significantly higher risk for CMR, with RRs ranging from 1.33 to 3.89 (all p < 0.001) for boys and from 1.63 to 3.16 (all p < 0.001) for girls. Notably, normal-weight boys with VFA above the cutoff had a significantly higher CMR risk compared to their peers in other weight status categories. Conclusions: Both the optimal and simplified VFA cutoffs are robust tools for screening CMR in Chinese children and adolescents, with significant implications for early intervention strategies.